From Traditional to Computational Archaeology. An Interdisciplinary Method and New Approach to Volume and Weight Quantification. Issue 4 (13th November 2018) - Moreno, Elena; Arévalo, Alicia; Moreno, José Francisco
Summary: The present study aims to show the effectiveness of a methodological procedure to estimate the volumetric capacity of archaeological ceramic vessels and the net and gross weights of their probable contents. This method can be easily applied, independently of cultural or chronological contexts, and, alongside other historical and economic conclusions, might serve to verify the possible existence of typological and metrological standardizations of domestic or commercial containers. This study gives a detailed description of a simple methodological protocol which uses profile drawings to calculate the approximate volume of any vessel, thus enabling assessment of its conformity to ancient weight systems. This article will illustrate the strength of the method using a sample of Ramon T‐11213 amphorae made in the Bay of Cadiz during the fifth century BC, which, given its quantitative and qualitative strengths, proves to be an exemplary case study and a valid pilot.